Low expression of TMPRSS2–a SARS-CoV-2 internalization protease–associates with basal subtype of head and neck squamous cell carcinoma - Tiwari J.; Tripathi N.; Srivastava R.S.; Kumar S.; Singh S.; Jain S.; Khattri A. (My University, 2025)
SARS-CoV-2 is a single-stranded RNA virus that has caused the ongoing COVID-19 pandemic. ACE2 and other genes utilized by SARS-CoV-2 to enter human cells have been shown to express in Head and Neck Squamous Cell Carcinoma (HNSCC) patients. However, their expression pattern in different subtypes has not been investigated. Hence, in the current study, we have analyzed the expression of ACE2, TMPRSS2 and FURIN in 649 HNSCC patients from two independent cohorts. Our analysis showed significantly lower expression of TMPRSS2 while significantly increased expression of ACE2 and FURIN in HPV-negative HNSCC. Comparison of expression of these genes in the three subtypes of HNSCC patients (basal, classical and inflamed/mesenchymal) showed no significant difference in the expression of ACE2 among the three subtypes; however, the basal subtype showed significantly reduced expression of TMPRSS2 but significantly increased expression of FURIN. Comparison of expression of these genes between the HPV-negative patients of basal subtype vs all others confirmed significantly lower expression of TMPRSS2 in HPV-negative patients of basal subtype as compared to all others. Our study shows that the different subtypes of HNSCC patients have different expression patterns of genes utilized by the SARS-CoV-2 to enter human cells, and hence, their susceptibility to SARS-CoV-2 may also be different. As the expression of TMPRSS2 is significantly lower in the HNSCC patients of the basal subtype, we predict that these patients would be less susceptible to SARS-CoV-2 infection than the patients of other subtypes. However, these findings need to be further validated. © 2022